A simple device for controlled feeding of pasty materials used as fermentation substrates - Hours, Roque Alberto (1985)
A simple device is described for con-trolled feeding of pasty materials in laboratory scale fed-batch cultures. The device was tested with apple pomace as raw material for production of microbial biomass, using the level of dissolved oxygen as controlled parameter.